Constructing A Pyramid of Income: A Model From Materialistic To Spiritual Concept - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2021)
The Objective of the study is to provide the understanding and interpret income not only in terms of material. Material income may be at the initial level of an individual or organization's income. Without realizing the increase in the level of individual income is not only seen from the rise in material income, but several aspects must be met by individuals and organizations so that it reaches a higher level of income that can be seen from the perspective of humanists, socialists, post-modernists, and spiritualists. The method of the study utilizes the spiritualist paradigm in nature. It is used to build a pyramid model of the income hierarchy. This brings several issues from the materiality aspect to the concept of spirituality. The result of the study is to construct a pyramid of income concepts. The pyramid of income is starting from materialistic, humanistic, socialist, postmodenist, to spiritualist income. The pyramid is derived from a broad range of social awareness. Materilistic income is understood as a physical value of money earned. Humanist income is viewed that income should be distributed to all people and no one left behind. Socialist income is meant by which income is controlled by a state and then distributed to the people. Postmodernist income is understood as harmonious income relationships between social environment and natural environment distributions. Spiritualist income is viewed as having relationship with the connectedness of human nad God.